Occupations of fathers of patients with Wilms's tumour. Issue 4 (December 1979) - Kantor, A F; Curnen, M G; Meigs, J W; Flannery, J T
Abstract : A case-control study of 149 Connecticut-born children with Wilms's tumour reported to the Connecticut Tumor Registry during the period 1935–1973 and of 149 matched controls was undertaken in order to explore the possibility that children with Wilms's tumour may have been exposed perinatally to carcinogenic agents. The occupation of the father at the time of the child's birth was investigated and used as an indicator of potential sources of carcinogens to which infants in the study may have been exposed. An association was found between paternal occupations related to lead in the group developing Wilms's tumour compared with the controls.